Safety and Role of Liver Biopsy in Diagnosing Liver Diseases Using a 5-Point Diagnostic Scale among Infants and Children - MD, Srikanth KP; DM,; MD, Uma Debi; MD, Jagadeesh Menon; DM,; MD, Lokesh Singh; MD, Sadhna B Lal; MD, Asim Das (Archives of Clinical and Medical Case Reports, 2020)
Introduction: Histological diagnosis is gold standard in many of the pediatric onset liver diseases. The safety and efficacy of the liver biopsy is less studied in infants and children, even though it is more often performed than in adult. We retrospectively reviewed the patients who had undergone percutaneous liver biopsy (LB) to assess the safety and role in the diagnosis of liver diseases. Patients and methods: A total of 234 cases of ultrasonography (USG) guided percutaneous LBs under the age of 20 years were performed (January 2013 to December 2015). The diagnostic yield was assessed in a 5-point scale [‘confirmed’, ‘confirmed, changed’, ‘supported’, ‘supported, changed’ and ‘no benefit’]. Results: Cholestasis of infancy was the most common indication (47.4%), followed by suspected glycogen storage disorder (14.1%) and rest were patients of chronic liver diseases of various etiologies. LB confirmed the specific etiologies of cholestasis of infancy in more than 90% of cases and the procedure was safe in young infants. Overall, most common confirmed etiologies confirmed were congenital hepatic fibrosis (16.2%), glycogen storage disorder (11.5%), progressive familial intrahepatic cholestasis (16.7%) and biliary atresia (6.4%). The proportion of confirmed cases were significantly more among infants < 3 months as compared to older children (82.6% vs. 39.7%; p<0.001). Conclusion: Liver biopsy in infants and children is a safe procedure, with high yield and very low rate of serious complication (1.2%). <gdiv></gdiv>